Characterizing the functions of Ty1 Gag and the Gag-derived restriction factor p22/p18. (3rd March 2016) - Pachulska-Wieczorek, Katarzyna; Błaszczyk, Leszek; Gumna, Julita; Nishida, Yuri; Saha, Agniva; Biesiada, Marcin; Garfinkel, David J.; Purzycka, Katarzyna J.
ABSTRACT: The long terminal repeat (LTR) and non-LTR retrotransposons comprise approximately half of the human genome, and we are only beginning to understand their influence on genome function and evolution. The LTR retrotransposon Ty1 is the most abundant mobile genetic element in the S. cerevisiae reference genome. Ty1 replicates via an RNA intermediate and shares several important structural and functional characteristics with retroviruses. However, unlike retroviruses Ty1 retrotransposition is not infectious. Retrotransposons integrations can cause mutations and genome instability. Despite the fact that S. cerevisiae lacks eukaryotic defense mechanisms such as RNAi, they maintain a relatively low copy number of the Ty1 retrotransposon in their genomes. A novel restriction factor derived from the C-terminal half of Gag (p22/p18) and encoded by internally initiated transcript inhibits retrotransposition in a dose-dependent manner. Therefore, Ty1 evolved a specific GAG organization and expression strategy to produce products both essential and antagonistic for retrotransposon movement. In this commentary we discuss our recent research aimed at defining steps of Ty1 replication influenced by p22/p18 with particular emphasis on the nucleic acid chaperone functions carried out by Gag and the restriction factor.